PHARMACEUTICAL EXCIPIENTS: GLOBAL REGULATORYISSUES - Dureja, Harish; Kumar, Dinesh (INDONESIAN JOURNAL OF PHARMACY, 2013)
An excipient may be defined as an ingredient that is intentionally added to a drug for purposes other than the therapeutic or diagnostic effect at the intended dosage. Excipients have functional roles in pharmaceutical dosage forms which include the suitable form of consistency, modulating solubility and bioavailability of active ingredients, enhancing stability of the active ingredients in finished dosage form and many others. In most of the developed countries, the excipients are regulated as an active pharmaceutical ingredient. In Europe, it is assumed that novel excipients need to be evaluated as new chemical entities. In United State, the Food and Drug Administration assesses and permits use excipients as part of new drug application. The lack of harmonized international regulatory guidelines leads to the formation of the International Pharmaceutical Excipients Council (IPEC) in 1991. The IPEC was found to calibrate with different countries like Japan, Europe and China to address prevalent industry concerns related to the international harmonization of excipients standards, the introduction of useful new excipients to market place, and development of safety evaluation guidelines for the excipients. In the present study, an attempt has been made to investigate global issues governing regulations of pharmaceutical excipients.Key words: pharmaceutical excipient, regulatory guidelines, IPEC